INFLUENCE OF UV RADIATION ON BIOLOGICAL PROPERTIES AND WATER ABSORPTION DURING PRE-SOWING IRRADIATION OF WINTER RAPESEEDS - Semenov, A. O.; Sakhno, T. V.; Semenova, N. V.; Liashenko, V. V. (Scientific Progress & Innovations, 2021)
At present, the studies of physiological and biochemical processes affecting seed germination, plant growth and their resistance to abiotic stresses are becoming topical. This stipulates the necessity of improving seed sowing qualities by improving the techniques of pre-sowing seed treatment using physical methods among which pre-sowing crop seed treatment with ultra-violet irradiation is considered the most effective. Owing to the impact of UV irradiation energy, metabolic processes between the cell and the environment are activated, ensuring quicker access of water and nutrients to the germ strengthening breathing and growth processes and creating favorable conditions for further plant growth and development. The influence of UV radiation of C region (200–280 nm) of Sherpa winter variety rapeseeds in pre-sowing treatment was investigated. In the work, the treatment was conducted with ZW20D15W ultra-violet lamps applying the following doses: 50, 120, 250, 500, 1000 and 3000 J/m2. Measuring UV-irradiation doses was made by “Tensor-31” radiometer produced at the scientific and production enterprise “Tensor”, Ukraine. It has been found that UV radiation has a positive effect on the sowing qualities of rapeseed when irradiated with doses of 120 J/m2: the germinating energy increased by 15 %, and the germinating capacity – by 11% as compared with the control samples. At irradiation doses of 250, 500, 1,000 and 3,000 J/m2, the decrease in the seeds sowing qualities is observed. The main parameters of hydration kinetic values were determined: moisture content and hydration rate. The study results have shown that hydro-priming increases the kinetics of water absorption, moreover, the rate of hydration increased sharply in the initial phase and gradually and slowly decreased in the middle and final phases of the hydration procedure. UV-irradiated seeds at a dose of 120 J/m2 showed faster penetration of water into the seeds and more effective tissue hydration, positively affecting the sowing qualities and biometrics in comparison with higher doses. It has been suggested that UV irradiation of rapeseeds in pre-sowing treatment can reduce excessive imbibition damage, since the germination potential decreases.